The Consequences of Modernity in the Deep Europe: The Transformation of Industrial Landscapes in Alpine Regions - Migliorati, Lorenzo; Veronesi, Liria (Italian Sociological Review, 2020)
The alpine region is undergoing a process of deindustrialization that has brought significant changes in the local communities; the large amount of brownfields in the Alps not only affects its economic growth but also the social context and the community development. This study aims to investigate the social fabric of a deindustrialised Austrian alpine community dealing with a brownfield regeneration process and to analyse the consequences of the industrial modernity from a social, cultural and symbolic perspective. For this, the wellbeing of the community in terms of social cohesion is examined as well as relevant identitarian aspects and representations of past and future. A mixed-methods research design is used and it combines data from structured questionnaire survey with data obtained by in-depth interviews and ethnographic fieldnotes.